Communism in Hollywood: The Moral Paradoxes of Testimony, Silence, and Betrayal - Casty, Alan, (Rowman & Littlefield Publishers, 2009)
Much has been written about the history of Communism in America, including the Party's appeal to many in the Hollywood community of the 1930s and 40s. While several books have offered standard accounts of the House Un-American Activities Committee (HUAC) hearings and the blacklist in the entertainment industry, Alan Casty provides a fresh and provocative perspective. In Communism in Hollywood: The Moral Paradoxes of Testimony, Silence, and Betrayal, Casty challenges the absolute dualisms of the period: cowardly informers and heroic martyrs. Drawing on newly available material, Casty illustrates the control by the international Communist movement and the role of the Hollywood Communists themselves in fomenting the intense hostilities of the period. Casty juxtaposes the actions and statements of those who testified and 'named names' before HUAC with Communists who refused to testify and remained silent about the atrocities of the Soviet Union. By providing a scrupulous account of the full scope of the Communist Party in Hollywood, this book presents a more accurate picture of the moral quandaries faced during this dark period in American history.